A bibliometric analysis of self-ordering systems research using vosviewer - Weny Aily Kho; Nadhira Felita Alisa; Wijaya Shofiy Indra; Wijaya Mahaning Indrawaty; Gunawan Ali (E3S Web of Conferences, 2024)
In this era of society, various sectors, including the food and beverage industry, are keen on integrating technological systems into their operational workflows to help the growth of the business itself. The adoption of technology systems in business processes, such as self-ordering system kiosks, tablets, or QR code menus, has become an emerging trend, including many stores, hotels, airports, and restaurants that eliminating inefficiency of manual ordering and reducing paper waste due to book menu. Many restaurants have been enabling customers to use a QR code method to order menus from their tables, which makes this study aim to examine the impact of self-ordering with QR codes within the scientific community. The literature review method is used in this research by analyzing 324 data encompassing a diverse range of sources, including articles, reviews, conference papers, books, and book chapters conducted since June 2023, spanning the publication years from 2018 to 2023. The analysis shows keywords related to self-service technology, technology acceptance, restaurant, etc. has been emerging trends within scientific community apart from there are gaps for further study. Nevertheless, self-ordering systems with QR codes are sought after for their potential to enhance efficiency and speed, reduce human error, save costs, improve the customer experience, and provide real-time order tracking. Using self-ordering is also related to the SDGs in improving industry, innovation, and infrastructure because it can support inclusive and sustainable industry.